ENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP MANAJEMEN PAJAK (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016) - Dwiputra, Reyhan Adiguna (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to examine and analyze the effect of institutional ownership, independent commissioners, and audit committees on tax management. Tax management is a means for carrying out taxation obligations optimally by reducing the amount of tax paid without violating the applicable rules. Tax management leads to a decrease in state’s revenues from taxation sector. This study uses secondary data with a sample of 43 manufacturing companies listed in the Indonesia Stock Exchange in the period of 2013-2016, which were determined through purposive sampling method. The data were analyzed using multiple regression analysis method. The results show that institutional ownership and independent commissioner have a significant and positive effect on tax management, while audit committee has no effect on tax managementKeywords: institutional ownership, independent commissioner, auditcommittee, tax management